NEUROPROTECTIVE EFFECTS OF AQUEOUS EXTRACT OF HYDROCOTYLE JAVANICA IN AMELIORATING NEUROBEHAVIORAL ALTERATION INDUCED BY MERCURY - Phukan, Pankaj; Namasudra, Sanjit; Bawari, Meenakshi; Sengupta, Mahuya (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study aims to assess the effects of the aqueous extract of Hydrocotyle javanica (HJ) in ameliorating mercury-induced neurobehavioral toxicity. Methods: For the study, 36 adult male Swiss albino mice of 25–30 g in weight were taken. They were equally divided into six groups. Group I was treated with distilled water, Group II was treated with mercuric chloride (1.5 mg/kg), Group III was treated with HJ extract low dose (100 mg/kg), Group IV was treated with HJ extract high dose (200 mg/kg), Group V was treated with mercuric chloride plus HJ extract low dose, and Group VI was treated with mercuric chloride plus TB extract high dose. In all the groups, the doses were administered orally through oral gavage tube and the treatment lasted for 14 days. The behavioral effects evaluated were locomotor activity in the open field test, immobility in forced swimming test and anxiety in elevated plus maze test, spatial learning ability, and memory in the Morris water maze test. Results: The present study showed that mercury exposure significantly decreased the locomotor activity (p<0.001), number of annulus crossovers (p<0.001), number of open arm entries (p<0.01), time spent in open arms (p<0.001), and increased escape latency (p<0.01), path length (p<0.001), and immobility (p<0.001) in mice. The aqueous extract of HJ significantly alleviated the neurotoxic effects of mercury. The aqueous extract of HJ showed to increase the locomotor activity (p<0.01), number of annulus crossovers (p<0.001), number of open arm entries (p<0.05), and time spent in open arms (p<0.05), which was decreased in mercury-exposed mice. The HJ extract also showed to decrease the immobility (p<0.001), escape latency (p<0.05), and path length (p<0.001) in mercury-exposed mice. Conclusion: The result of the study shows that neurobehavioral changes induced by mercuric chloride were significantly reversed by the aqueous extract of HJ. Thus, base on the present study, it is concluded that HJ is effective in ameliorating the neurobehavioral deficits induced by mercury.